Politics, property, and progress - Gallop, G; G. I. Gallop (1983)
﻿ This thesis attempts to provide an account of radical thought in Britain, 1760 to 1815, by way of a study of the tracts, pamphlets and articles of the major radical ideologues. It begins by examining the assumptions made by the radicals in respect of nature and human nature, material and moral progress, and liberty and equality. The differences revealed in relation to the basic assumptions are then analysed in the context of the major questions of politics, property and progress. On the issue of political liberty distinctions are made between mixed constitutionalist radicals and republicans, democratic or otherwise, and between those who adopted a "radical" as opposed to a "moderate" approach to voting rights. Special attention is given to Thomas Spence's and William Godwin's views on decentralization and democracy and to the radical case for an armed citizenry. Regarding property and progress a major distinction is drawn between agrarian and commercial radicals according to attitudes taken on the emergence and development of modern commercial society. The different versions of the agrarian alternative are considered and the reformist, communitarian and revolutionary approaches to agrarianism examined. In relation to commercial radicalism a distinction is drawn between Smithian and artisan approaches to the meaning of equality of opportunity and connected with a change in the social composition of the radical movement in the 1790s. A chapter is devoted to James Burgh who synthesized aspects of agrarianism and commercial radicalism. The final section of the thesis considers the alternatives proposed for the achievement of radical ends. A distinction is drawn between reformers and revolutionaries and two chapters given over to consideration of the special contributions of William Godwin and the young Coleridge. It is concluded that radical ideology is best understood as a synthesis of civic humanism and Lockean liberalism and that the class perceptions of particular radicals are important in understanding the different ways they develop the radical case.